Determining the Cause-And-Effect Relationships Responsible for Coal Properties 4. Assessing the Influence of Mineral Impurities on the Organic Mass of Coal - Ivanov V. P. Vladimir Petrovich; Isaeva E. R. Elena Rinatovna; Chegodaeva N. A.; Podchishchaeva N. I.; Surovtseva I. V. (2017, 2017)
Title screen